Current status and challenges of diagnosis and treatment of hyperthyroidism in China - LI Jing, SHAN Zhongyan (Zhenduanxue lilun yu shijian)
In China, the clinical prevalence of hyperthyroidism is 0.78%, subclinical hyperthyroidism is 0.44%, and Graves' disease hyperthyroidism is 0.53%. Untreated hyperthyroidism and subclinical hyperthyroidism may increase the risk of atrial fibrillation, stroke, and other cardiovascular events, as well as osteoporosis and fractures. In special populations (such as pregnant women and the elderly), both the diagnosis and treatment of hyperthyroidism require special conside-rations. Although China has made some progress in the standardized diagnosis and treatment of hyperthyroidism, challenges remain. Despite established guidelines for diagnosis and differential diagnosis, clinical practice faces obstacles, notably due to limited access to thyroid radionuclide imaging and 131 iodine uptake rate in some hospitals. Additionally, the peak systolic velocity (PSV) in the thyroid obtained by thyroid ultrasound is not widely adopted. While clinical treatment methods align with international standards in China, there is a lack of specific guidelines on the initial dose and dose adjustment during the reduction period of antithyroid drugs (ATD). Currently, most clinicians follow the initial dose regimen re-commended by the guidelines established by the American Thyroid Association. Furthermore, indicators in both domestic and international guidelines for predicting adverse reactions to ATD remain unclear. During the ATD treatment of hyperthyroidism, the incidence of transient neutropenia is 1%-5%, and follow-up of baseline blood routine and liver function is ne-cessary. At present, there is a lack of monitoring frequency regulations and high-quality evidence-based medical support for above indice, and clinical practice has not yet established feasible indicators for predicting ATD adverse reactions. ATD-induced agranulocytosis is related to genetic susceptibility, age, drug type and dosage. HLA-B*27:05, HLA-B*38:02 and HLA-DRB1*08:03 on chromosome 6 in Chinese Han population may be susceptibility genes. Progress has been made in the diagnosis and treatment of thyroid associated ophthalmopathy (TAO) in China, with 36.7% of doctors adopting a multidisciplinary approach. Due to accessibility issues, less than 10% of patients receive biological agents to treat TAO, which is significantly lower than that in Western countries. Given these current status and challenges in China, further measures are necessary to improve the diagnosis and treatment of hyperthyroidism.